The IMPLICATIONS OF THE HISTORICAL BASIS OF PAI CURRICULUM DEVELOPMENT IN THE MODERN ERA: IMPLIKASI LANDASAN HISTORIS PENGEMBANGAN KURIKULUM PAI DI ERA MODERN - Sisin Warini; Firani Putri; Arifmiboy Arifmiboy (Sekolah Tinggi Ilmu Tarbiyah (STIIT) Ahlussunnah Bukittinggi, 2023)
The education curriculum in Indonesia in its journey has made various developments ranging from centralization, decentralization and autonomy to education and always experiences innovation every year. Curriculum development is very important in line with advances in science, technology, arts and culture, and changes in society. In line with the development of Islamic education, especially when Islamic education is carried out in the form of formal educational institutions, the content of the Islamic education curriculum has developed. The research method uses the library study method. This development and change in the national curriculum has also resulted in a change in the Islamic education curriculum in Indonesia. The historical basis for the development of the PAI curriculum refers to various historical experiences that have influenced the developed curriculum. The details are the 1947 Curriculum, 1964 Curriculum, 1968 SD Curriculum, 1973 PPSP Curriculum, 1975 SD Curriculum, 1984 Curriculum, 1994 Curriculum, 1997 Curriculum Revision, 2004 Competency Based Curriculum (KBK), Lesson Unit Level Curriculum (KTSP) ) in 2006, Curriculum 2013 and Curriculum Merdeka.